The Analysis of Investment Environment and Foreign Direct Investment Prognostication: Lithuanian Case - Gaspareniene, Ligita (Economics and Business, 2015)
The aim of this article is to research the investment environment and to prognosticate the trends of FDI in Lithuania. The methods of the research include systematic and comparative analysis of the scientific literature and linear regression and trend analysis. The results of the research have revealed that the trend and amount of FDI in Lithuania strongly correlate. The linear regression equation is also growing, which proposes that over the next two years FDI in Lithuania should increase.